ВПЛИВ ПОХИБКИ ПРОГНОЗУВАННЯ ШВИДКОСТІ ВІТРУ НА ВЕЛИЧИНУ ЗОНИ КЕРОВАНОЇ РОБОТИ НАКОПИЧУВАЧА В СИСТЕМІ З ВІТРОГЕНЕРАТОРОМ - Клен, К.С.; Яременко, М.К.; Жуйков, В.Я. (Інститут електродинаміки Національної академії наук України, 2020)
The article analyzes the influence of wind speed prediction error on the size of the controlled operation zone of the storage. The equation for calculating the power at the output of the wind generator according to the known values of wind speed is given. It is shown that when the wind speed prediction error reaches a value of 20%, the controlled operation zone of the storage disappears. The necessity of comparing prediction methods with different data discreteness to ensure the minimum possible prediction error and determining the influence of data discreteness on the error is substantiated. The equations of the "predictor-corrector" scheme for the Adams, Heming, and Milne methods are given. Newton's second interpolation formula for interpolation/extrapolation is given at the end of the data table. The average relative error of MARE was used to assess the accuracy of the prediction. It is shown that the prediction error is smaller when using data with less discreteness. It is shown that when using the Adams method with a prediction horizon of up to 30 min, within ± 34% of the average energy value, the drive can be controlled or discharged in a controlled manner. Ref. 13, fig. 2, tables 3.